Embedding and Leveraging: The Implementation Mechanism of Routine-Formalized Central Tasks - Ruiyang Zhou (International Journal of Social Sciences and Public Administration, 2026)
Central tasks and routine tasks together constitute the primary governance affairs of local governments. The process by which central tasks are transformed into routine tasks manifests as a transitional form-the routine-formalized central task. Using the creation and consolidation of a National Civilized City in District A as a case study, this research finds that routine-formalized central tasks retain the characteristics of central tasks while relying on the orderly operation of the bureaucratic system, exhibiting three practical features: flexible organizational structures, contracted responsibility networks, and phased pressure transmission. In terms of implementation strategies, local governments achieve sustainable advancement and legitimization of tasks through two pathways: embedding into the routine system and leveraging momentum from central tasks. The operational logic of this transitional form shifts from "compliance competition" to risk avoidance, and is regulated by periodic review inspections. This approach overcomes the unsustainability of campaign-style governance while avoiding the potential inertia of conventional bureaucracy. This study fills a gap in existing research regarding the transitional form of central-to-routine task transformation, offering a new perspective for understanding the flexibility and effectiveness of local governance in China.